Cambios en el periodismo y su impacto en la autonomía profesional: evidencia del estudio The Worlds of Journalism en siete países de América LatinaA New Route of Valorization of Petrochemical Wastewater: Recovery of 1,3,5-Tris (4-tert-butyl-3-hydroxy-2,6-dimethyl benzyl)–1,3,5-triazine-2,4,6-(1H,3H,5H)-trione (Cyanox 1790) and Its Subsequent Application in a PP Matrix to Improve Its Thermal Stability (2023)
The various chemicals in industrial wastewater can be beneficial for improving its circularity. If extraction methods are used to capture valuable components from the wastewater and then recirculate them throughout the process, the potential of the wastewater can be fully exploited. In this study, wastewater produced after the polypropylene deodorization process was evaluated. These waters remove the remains of the additives used to create the resin. With this recovery, contamination of the water bodies is avoided, and the polymer production process becomes more circular. The phenolic component was recovered by solid-phase extraction and HPLC, with a recovery rate of over 95%. FTIR and DSC were used to evaluate the purity of the extracted compound. After the phenolic compound was applied to the resin and its thermal stability was analyzed via TGA, the compound’s efficacy was finally determined. The results showed that the recovered additive improves the thermal qualities of the material.